Implementation of Six Sigma Philosophy and 6s Principles on Bag Making Warehouse at PT. X - Adiguna, Luke Pratama; Rahardjo, Jani (RSF Conference Series: Business, Management and Social Sciences, 2022)
PT. X is a company specializing in rotogravure printing, laminating, and flexible packaging. One of the divisions in PT. X is the bag making division. The division is in charge of processing the print roll using machine to become shape of a bag. After the process, all of the excess bags that are not sent to the customer are kept in a box and then put in an area designated for storage. Even though the company has already set a designated place for the excess products, there is no warehouse monitoring system implemented in that area. Consequently, the items inside are stacking up day by day, causing the area to be overloaded making it hard to organize the boxes and makes it hard to go into the area. This research will try to solve the problem stated above using DMAIC (Define, Measure, Analyze, Improve, Control) methodology. The improvements in this research will be based on the 6S (Sort, Set in order, Shine, Standardize, Sustain, Safety) principles of lean manufacturing. The results are improved search time and accuracy, also conformity to the 6S of lean manufacturing principles.